2009
DOI: 10.1021/ja9036127
|View full text |Cite
|
Sign up to set email alerts
|

The Ru−Hbpp Water Oxidation Catalyst

Abstract: A thorough characterization of the Ru-Hbpp (in,in-{[Ru(II)(trpy)(H(2)O)](2)(mu-bpp)}(3+) (trpy is 2,2':6',2''-terpyridine, bpp is bis(2-pyridyl)-3,5-pyrazolate)) water oxidation catalyst has been carried out employing structural (single crystal X-ray), spectroscopic (UV-vis and NMR), kinetic, and electrochemical (cyclic voltammetry) analyses. The latter reveals the existence of five different oxidation states generated by sequential oxidation of an initial II,II state to an ultimate, formal IV,IV oxidation sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
213
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 255 publications
(220 citation statements)
references
References 61 publications
5
213
1
1
Order By: Relevance
“…[150] However,B ozoglian et al found that the barrier for water insertionf rom the peroxide intermediate was associatedw ith ab arriero f 27.1 kcal mol À1 , [73] which was much lower than that found by Yang andB aik. [150] The differencew as suggestedt oc ome from the different density functional used, B3LYP versus M06L.…”
mentioning
confidence: 88%
“…[150] However,B ozoglian et al found that the barrier for water insertionf rom the peroxide intermediate was associatedw ith ab arriero f 27.1 kcal mol À1 , [73] which was much lower than that found by Yang andB aik. [150] The differencew as suggestedt oc ome from the different density functional used, B3LYP versus M06L.…”
mentioning
confidence: 88%
“…Formation. Accumulated experimental and theoretical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) on artificial photosynthesis systems have elucidated dual possible mechanisms of the water splitting reaction: (i) the radical coupling (RC) mechanism and (ii) the acid-base mechanism. Tanaka and coworkers have proposed the former mechanism for the water splitting reaction by their Ru-quinone complexes as illustrated in Fig.…”
Section: Possible Electronic and Spin States Of Mononuclear And Binucmentioning
confidence: 99%
“…In the past decades, a number of experimental and theoretical studies (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) have been performed to design artificial photosynthetic systems that mimic native PSII systems. Many binuclear transition-metal catalysts such as LðH 2 OÞM-O-MðOH 2 ÞL or LðH 2 OÞM-BL-MðOH 2 Þ (where L and BL are nonbridging and bridging organic ligands, respectively) were prepared and characterized for their catalytic properties toward water oxidation (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…18,19,20,21,22 When combined with the theoretical analysis, via density functional theory (DFT) calculations, spectroscopic and electrochemical measurements provide detailed information on the nature of reaction intermediates and activation free energies along the catalytic cycle of water oxidation. 23,24,25,26,27,28,29,30 Strong sigma donation groups like carboxylate ligands in 2,2'-bipyridine-6,6'-dicarboxylic acid (H 2 bda; see Chart 1 for a drawing), together with seven coordination have allowed easy access to reactive species in high oxidation states such as [Ru V (O)(bda)(pic) 2 ] + (pic is 4-picoline) where the metal center is at formal oxidation state of V. 31 Additional tuning of the activation energy barriers can result from supramolecular interactions, based on π-π stacking of ligands with π -extended conjugation such as isoquinoline and its derivatives favoring formation of dinuclear peroxo intermediates. 32,33 Furthermore, hydrogen bonding interactions can play a significant role in the kinetics as demonstrated with strategically substituted fluro-2,2'-bpy ligands.…”
Section: Introductionmentioning
confidence: 99%